A Bag of Beads Or a Necklace? Combinative Capability and Value in Technological Scope Expansions - Lee, Jeongsik Jay; Balasubramanian, Natarajan (Disruptive Innovation in Business and Finance in the Digital World, 2019)
Abstract The authors study the relation between a firm’s combinative capability and value creation in the context of technological scope expansion. On a sample of Compustat firms that applied for US patents between 1980 and 2001, the authors find that firm value, measured using Tobin’s q, decreases with increases in technological scope (measured as the number of unique patent classes). However, when firms expand by combining different classes into a single patent, the authors find that this negative effect is significantly diminished. These findings indicate that increasing technological scope likely creates value only when the firm is able to integrate the components into a single technology; simply maintaining different technological components within the firm boundary without integration appears to subject the firm to a discount.